The global stability and pattern formations of a predator–prey system with consuming resource. (August 2016) - Fang, Liting; Wang, Jinfeng
Abstract: The paper deals with a model that describes a predator–prey system with a common consuming resource. We use Lyapunov functions to prove the global stability of the kinetic system and the diffusive system. The existence of non-constant positive steady state solutions is shown to identify the range of parameters of spatial pattern formation for the cross-diffusion system.